Synthetic method of metal oxide material
The preparation of multivariate amorphous metal oxides at room temperature by liquid phase co-precipitation method solves the problems of complex process and difficult to control material uniformity in traditional methods, and achieves low-cost and high-efficiency amorphous material preparation, which is suitable for catalysts and other applications.
Patent Information
- Application Number
- CN202510380108.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-27
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-03-27
AI Technical Summary
When traditional methods are used to synthesize multivariate amorphous metal oxide materials, they face complex process flow, difficulty in controlling the uniformity and consistency of materials, and difficulty in effectively controlling diffusion entropy and vibration entropy during the crystal and amorphous conversion process.
By using the liquid phase co-precipitation method, the reaction is carried out to prepare a polymorphic amorphous metal oxide by dissolving the metal salt of more than five metal elements in a reducing substance containing ethanol groups, adding tannin acid as a reducing agent, and then sodium hydroxide or potassium hydroxide as a base.
It realizes the preparation of uniform amorphous multi-oxides at room temperature at a simple and low cost, with the characteristics of adjustable structural sequence and customized, suitable for catalyst and other applications, and has simple process operation, short production cycle and low energy consumption.
Smart Images

Figure CN119873751A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of oxide materials, and in particular relates to a method for preparing or synthesizing a metal oxide material (multinary amorphous metal oxide). Background Art
[0002] As an important functional material, metal oxide materials have played an indispensable role in catalysis, energy conversion, environmental protection and other fields due to their unique physical and chemical properties. Based on advanced material design concepts, this type of material can be given more excellent performance by adjusting its composition and structure. Specifically, oxide materials with adjustable chemical order structures introduce a variety of metal elements and combine them in specific proportions to form a high configuration entropy system, thereby achieving precise control of material stability and functionality. This structural stability stems from the random distribution of multiple elements in the oxide lattice, which significantly increases the configuration entropy of the system, thereby improving the overall stability of the material. Compared with traditional oxide materials, oxides with adjustable chemical order structures not only have significantly improved structural complexity, but also show unique advantages in electronic structure and thermodynamic properties, and are suitable for a variety of application scenarios.
[0003] In order to optimize the performance of this type of oxide material, it is necessary to start from the entropy effect and precisely control the type and proportion of metal elements by regulating the entropy of the components. The synergistic effect of different metal ions in the lattice allows the electronic structure and energy band characteristics to be flexibly adjusted, thereby improving the performance of materials in catalysis, electrochemical energy storage and other fields. In addition, the performance regulation of metal oxide materials not only depends on the component entropy, but also includes the control of diffusion entropy and vibration entropy. By adjusting the diffusion entropy, the material can be controlled to transform between the crystalline and amorphous states, thereby affecting its microstructure and system stability. For example, in an amorphous structure, short-range order and long-range disorder coexist, giving the material a higher structural relaxation and adaptability, thereby exhibiting more stable and flexible physical and chemical properties.
[0004] Although this type of oxide material has shown great application potential, its synthesis still faces many challenges. Traditional solid-phase and liquid-phase synthesis methods are relatively complex and often require strict experimental conditions, which makes it difficult to control the uniformity and consistency of the material. In addition, the interactions between atoms in multi-component systems are complex, and the regulation of enthalpy and entropy is difficult. Especially in the process of transformation between crystalline and amorphous states, how to effectively control diffusion entropy and vibration entropy is still a difficult problem in the synthesis of multi-component amorphous metal oxide materials. Therefore, it is particularly important to develop a new method that is simple in process, low in cost, and can prepare this type of metal oxide in batches. This method can reduce production costs, improve production efficiency, and help realize the large-scale application of materials in industry, providing new opportunities for further promoting the development of materials science and technology. Summary of the invention
[0005] In view of this, the present invention provides a method for synthesizing a metal oxide material, which can produce multinary amorphous metal oxides, has low cost, simple and easy operation, short production cycle, low energy consumption, and certain adjustability.
[0006] The present invention provides a method for synthesizing a metal oxide material, comprising the following steps:
[0007] Step 1, selecting metal salts corresponding to five or more metal elements, dissolving all of the metal salts in a reducing substance containing an ethanol group, and stirring until the metal salts are completely dissolved to form a solution; the metal elements are Li, Na, K, Mg, Ca, Al, Ti, Cr, Mn, Fe, Co, Ni, Cu, Zn, Sr, Zr, Nb, Mo, Ru, Rh, Pd, Cd, Sn, Cs, La, Ba, Ce, Nd, W, Re, Ir, Pt and Bi;
[0008] Step 2, adding tannic acid as a reducing agent into the solution, and continuously stirring to form a mixed solution;
[0009] Step three, adding a base to the mixed solution for reaction, wherein the base is sodium hydroxide and / or potassium hydroxide, and separating to obtain a multinary amorphous metal oxide.
[0010] The basic principle of the embodiment of the present invention includes: in the present invention, tannic acid is selected as a reducing agent, which forms a strong reducing environment together with ethanol or its derivatives that also have reducing properties, which can overcome the difference in electron density between some metal ions and simultaneously reduce a variety of different metal ions to dispersed monomers. When the metal salt precursor enters the solution, its relatively stable state is destroyed. Since the concentrations of various element monomers are almost uniform, the metal elements are finally randomly distributed. At the same time, the reaction can occur in a very short time. In the process of limited atomic monomer diffusion and rapid nucleation, due to the different distributions of different monomers and differences in diffusion kinetics, it is difficult to form long-range order, and the system energy is finally in a metastable state, realizing the non-equilibrium synthesis of metal oxides.
[0011] In a specific embodiment of the present invention, a variety of metal salts can be weighed, dissolved in a reducing substance containing a hydroxyl functional group, and stirred for 2-60 minutes until the metal salts are completely uniform, thereby obtaining a stable solution containing metal salts.
[0012] In the step 1, the metal salt is one or more of a metal hydrochloride (chloride), nitrate, nitrite, sulfate and acetylacetonate; specifically, it may be a chloride, nitrate or acetylacetonate (such as Pd(acac)2), and some of them are hydrates. Preferably, the concentration of each metal in the ethanol or its derivative is 4 g·L-1 .
[0013] The metal elements are composed of five or more elements selected from lithium (Li), sodium (Na), potassium (K), magnesium (Mg), calcium (Ca), aluminum (Al), titanium (Ti), chromium (Cr), manganese (Mn), iron (Fe), cobalt (Co), nickel (Ni), copper (Cu), zinc (Zn), strontium (Sr), zirconium (Zr), niobium (Nb), molybdenum (Mo), ruthenium (Ru), rhodium (Rh), palladium (Pd), cadmium (Cd), tin (Sn), cesium (Cs), lanthanum (La), barium (Ba), cerium (Ce), neodymium (Nd), tungsten (W), rhenium (Re), iridium (Ir), platinum (Pt), and bismuth (Bi); the types and proportions of the elements can be adjusted arbitrarily, and specifically can be equal in mass. Furthermore, the metal elements are at least five of Mg, Ca, Al, Ti, Cr, Mn, Fe, Co, Ni, Cu, Zn, Sr, Zr, Nb, Mo, Ru, Rh, Pd, Cd, Sn, Cs, La, Ba, Ce, Nd, W, Re, Ir and Pt.
[0014] In some embodiments, the metal elements include: Mg, Al, Ca, Cr, Mn, Fe, Co, Ni, Cu, Zn, Sr, Zr, Nb, Mo, Ru, Rh, Pd, Cd, Sn, Ba, Ce, W, Ir, Pt (a total of 24 elements); or, the metal elements include: Mg, Al, Ca, Cr, Mn, Fe, Co, Ni, Cu, Zn, Zr, Nb, Ru, Cd, Ce, Ir (a total of 16 elements). In other embodiments, the metal elements include Cr, Fe, Co, Ni and Cu, or include Mn, Fe, Co, Ni, Cu.
[0015] In the step 1, the reducing substance containing a hydroxyl functional group is a solvent, preferably one of ethylene glycol, ethanol, ethanolamine, β-mercaptoethanol and diethylene glycol, further ethylene glycol or diethylene glycol.
[0016] Step 2 of the embodiment of the present invention is to add tannic acid to the aforementioned solution and continue stirring to keep the mixed solution uniform. Tannic acid, also known as tannic acid, tannin, etc., is a polyphenol substance widely distributed in plants; in the embodiment of the present invention, it is C 76 H 52 O 46 (reagent grade, 98%).
[0017] In step 2, the concentration of tannic acid in the mixed solution is 0.1-5 g / L; in the solution after adding tannic acid, the concentration of tannic acid can be 0.5-3 g·L -1 , specifically 2g / L.
[0018] After obtaining the mixed solution, the specific embodiment of the present invention can slowly add an alkaline solution of sodium hydroxide / potassium hydroxide (preferably adding an aqueous sodium hydroxide solution) and continue stirring for at least 5 minutes to promote the reaction. The actual reaction time of the embodiment of the present invention is very short, almost instantaneous after the addition of the alkaline solution. The purpose of controlling a certain stirring time is to promote the full progress of the reaction; the reaction is carried out at room temperature. The embodiment of the present invention prepares a multinary amorphous metal oxide by liquid phase reaction, and in its amorphous structure, short-range order and long-range disorder coexist.
[0019] In the step 3, it is preferred to add an alkaline solution with a concentration of 0.1-10 mol / L to the mixed solution, and react under stirring conditions; the concentration of the added sodium hydroxide solution may be 0.5-2 mol / L, specifically 1 mol / L.
[0020] In the step three, after the reaction, the final product is collected by centrifugation to remove impurities in the solution; the sample is washed with water several times to ensure that no alcohol or its derivatives remain in the sample, and dried to obtain a dry multi-element amorphous metal oxide containing multiple metal elements.
[0021] In the step 3, the centrifugal separation is carried out at a speed of 7000-8000 rpm for 5-10 minutes, and the mixture is washed with water for 5-10 times. Preferably, the centrifugal separation and washing with water are carried out at a speed of 8000 rpm for 5 minutes, and the mixture is washed with deionized water for 8 times.
[0022] In step 3, the drying includes: placing the product after washing with water under vacuum drying at 50-90°C to remove the remaining solvent overnight (12 hours) to obtain the sample material. The drying temperature can be 60-80°C.
[0023] Compared with the prior art, the present invention has the following technical effects: the synthesis method of the metal oxide material in the embodiment of the present invention adopts the liquid phase coprecipitation method, which realizes the simple preparation of uniform amorphous multi-element oxides at room temperature. It is a low-cost, energy-saving, high-production efficiency, and simple process synthesis method; the present invention provides a new idea for the batch preparation of amorphous metal oxides. The synthesis method in the present invention covers 33 kinds of metal elements and has a certain universality; at the same time, it can also be independently selected from the elements according to application requirements, and has the characteristics of customized synthesis. The metal oxide synthesized in the present invention has the characteristics of adjustable structural order. By controlling the diffusion rate of atomic monomers in the rapid nucleation process, selective synthesis from crystalline to amorphous can be achieved.
[0024] In summary, the present invention has developed a universal synthesis strategy for a multinary amorphous metal oxide material with adjustable structural order and customizable elemental composition. The material has a nanomorphology (the material size is about 500nm under a transmission electron microscope) and can be used as a catalyst. The method of the present invention has low cost, simple process operation, short production cycle, low energy consumption, and high efficiency, and can be customized and mass-produced. It is a synthesis strategy for metal oxide nanocatalysts. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0026] Figure 1 XRD results of the multi-element amorphous metal oxide containing Mg, Al, Ca, Cr, Mn, Fe, Co, Ni, Cu, Zn, Sr, Zr, Nb, Mo, Ru, Rh, Pd, Cd, Sn, Ba, Ce, W, Ir, and Pt elements obtained in Example 1;
[0027] Figure 2 XRD results of the multi-element amorphous metal oxide containing Mg, Al, Ca, Cr, Mn, Fe, Co, Ni, Cu, Zn, Zr, Nb, Ru, Cd, Ce and Ir elements prepared in Example 2;
[0028] Figure 3 The metal element distribution diagram of the multi-component amorphous metal oxide containing Mg, Al, Ca, Cr, Mn, Fe, Co, Ni, Cu, Zn, Zr, Nb, Ru, Cd, Ce, and Ir elements prepared in Example 2;
[0029] Figure 4 The XRD results of the multi-component amorphous metal oxide containing Cr, Fe, Co, Ni and Cu elements in Example 3;
[0030] Figure 5 The XRD results of the multi-component amorphous metal oxide containing Mn, Fe, Co, Ni and Cu elements in Example 4 are shown;
[0031] Figure 6 The XRD result of the amorphous metal oxide containing Ru element in Comparative Example 1;
[0032] Figure 7 is a metal element distribution diagram of the amorphous metal oxide containing Ru element in Comparative Example 1;
[0033] Figure 8 The XRD result of the crystalline metal oxide containing Cu element in Comparative Example 2;
[0034] Fig. 9 The XRD result of the amorphous metal oxide containing Cu element in Comparative Example 3;
[0035] Fig.10 The XRD results of the multi-component amorphous metal oxide containing Fe, Co, Ni, Cu and Pd elements in Example 5;
[0036] Fig.11 The metal element distribution diagram of the multi-component amorphous metal oxide containing Fe, Co, Ni, Cu and Pd elements in Example 5;
[0037] Fig.12 1 is the XRD result of the amorphous metal oxide containing Co element in Comparative Example 4. DETAILED DESCRIPTION
[0038] In order to further understand the present invention, the preferred embodiments of the present invention are described below in conjunction with examples. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the present invention.
[0039] In order to better illustrate the present invention, the following examples are further illustrated. In the examples, all raw reagents and materials are commercially available, and the experimental methods without specific experimental conditions are conventional methods and conditions well known in the art.
[0040] Example 1
[0041] Weigh 0.05 g each of MgCl2·6H2O, AlCl3·6H2O, CaCl2, CrCl3·6H2O, MnCl2·4H2O, FeCl3·9H2O, CoCl2·6H2O, NiCl2·6H2O, CuCl2·2H2O, ZnCl2, SrCl2·6H2O, ZrCl4, NbCl5, MoCl5, RuCl3·H2O, RhCl3, PdCl2, CdCl2, SnCl4, BaCl2·2H2O, CeCl3·6H2O, WCl6, IrCl3·xH2O, and PtCl2, and dissolve them in 240 mL of ethylene glycol. Stir well to obtain a solution containing metal salts. Then weigh 480 mg of tannic acid and add it to the above solution. Stir well and add 12 mL of 1.0 mol·L -1of sodium hydroxide solution; continue the reaction and stir at room temperature for 60 minutes to promote the reaction to proceed fully. The solution after the above reaction was centrifuged at a speed of 8000 rpm for 5 minutes, washed with deionized water 8 times (the same as in the following examples), and finally the washed product was placed in a vacuum dryer at 80°C overnight to obtain a multi-element amorphous metal oxide containing Mg, Al, Ca, Cr, Mn, Fe, Co, Ni, Cu, Zn, Sr, Zr, Nb, Mo, Ru, Rh, Pd, Cd, Sn, Ba, Ce, W, Ir, and Pt elements (1.91g product was obtained).
[0042] Figure 1 There is no obvious diffraction peak in the X-ray diffraction (XRD) pattern, which proves the amorphous structure of the substance.
[0043] Example 2
[0044] Weigh 0.05 g each of MgCl2·6H2O, AlCl3·6H2O, CaCl2, CrCl3·6H2O, MnCl2·4H2O, FeCl3·9H2O, CoCl2·6H2O, NiCl2·6H2O, CuCl2·2H2O, ZnCl2, ZrCl4, NbCl5, RuCl3·H2O, CdCl2, CeCl3·6H2O, and IrCl3·xH2O, and dissolve them in 160 mL of ethylene glycol. Stir well to obtain a solution containing metal salts. Then weigh 320 mg of tannic acid and add it to the above solution. Stir well and add 8 mL of 1.0 mol·L -1 The reaction was continued and stirred at room temperature for 60 minutes to promote the reaction to proceed fully. The solution after the reaction was centrifuged and washed several times with deionized water. Finally, the washed product was placed in a vacuum dryer at 80°C overnight to obtain a multi-element amorphous metal oxide containing Mg, Al, Ca, Cr, Mn, Fe, Co, Ni, Cu, Zn, Zr, Nb, Ru, Cd, Ce, and Ir elements.
[0045] Figure 2 There is no obvious diffraction peak in the XRD diffraction pattern, which proves the amorphous structure of the material. Figure 3 The metal element distribution diagram shows that all metal elements are evenly distributed in the sample material.
[0046] Example 3
[0047] Weigh 0.2 g each of CrCl3·6H2O, FeCl3·9H2O, CoCl2·6H2O, NiCl2·6H2O, and CuCl2·2H2O, and dissolve them in 200 mL of ethylene glycol. Stir evenly to obtain a solution containing metal salts. Then weigh 400 mg of tannic acid and add it to the above solution. Stir evenly and add 10 mL of 1.0 mol·L -1 The sodium hydroxide solution was added; the reaction was continued and stirred at room temperature for 30 minutes to promote the reaction to proceed fully. The solution after the reaction was centrifuged and washed with deionized water several times. Finally, the washed product was placed in a vacuum dryer at 80°C overnight to obtain a multi-element amorphous metal oxide containing Cr, Fe, Co, Ni, and Cu elements.
[0048] Figure 4 There is no obvious diffraction peak in the XRD diffraction pattern, which proves the amorphous structure of the material.
[0049] Example 4
[0050] Weigh 0.2 g each of MnCl2·4H2O, FeCl3·9H2O, CoCl2·6H2O, NiCl2·6H2O, and CuCl2·2H2O, and dissolve them in 200 mL of ethylene glycol. Stir evenly to obtain a solution containing metal salts. Then weigh 400 mg of tannic acid and add it to the mixed solution. Stir evenly and add 10 mL of 1.0 mol·L -1 The reaction was continued and stirred at room temperature for 30 minutes to promote the reaction to proceed fully. The solution after the reaction was centrifuged and washed with deionized water several times. Finally, the washed product was placed in a vacuum dryer at 80°C overnight to obtain a multi-element amorphous metal oxide containing Mn, Fe, Co, Ni, and Cu elements.
[0051] Figure 5 There is no obvious diffraction peak in the XRD diffraction pattern, which proves the amorphous structure of the material.
[0052] Comparative Example 1
[0053] Weigh 0.2 g of RuCl3·H2O and dissolve it in 40 mL of ethylene glycol. Stir well to obtain a solution containing metal salts. Then weigh 80 mg of tannic acid and add it to the above solution. Stir well and add 2 mL of 1.0 mol·L -1 The reaction was continued and stirred at room temperature for 5 minutes to promote the reaction to proceed fully. The above solution was centrifuged and washed with deionized water several times, and finally the washed product was placed in a vacuum dryer at 80°C overnight to obtain an amorphous metal oxide containing Ru element.
[0054] Figure 6There is no obvious diffraction peak in the XRD diffraction pattern, which proves the amorphous structure of the substance; Figure 7 As for its metal element distribution, it shows that the metal element Ru is evenly distributed in the sample material.
[0055] Comparative Example 2
[0056] Weigh 0.2 g of CuCl2·2H2O and dissolve it in 40 mL of ethylene glycol. Stir well to obtain a solution containing metal salts. Then weigh 80 mg of tannic acid and add it to the mixed solution. Stir well and add 10 mL of 1.0 mol·L -1 The reaction was continued and stirred at room temperature for 5 minutes to promote the reaction to proceed fully. The above solution was centrifuged and washed with deionized water several times, and finally the washed product was placed in a vacuum dryer at 80°C overnight to obtain a crystalline metal oxide containing Cu element.
[0057] Figure 8 The obvious diffraction peaks in the XRD diffraction pattern prove the CuO crystalline structure of the material.
[0058] Comparative Example 3
[0059] Weigh 0.2 g of Cu(NO3)2·2H2O and dissolve it in 40 mL of ethylene glycol. Stir well to obtain a solution containing metal salts. Then weigh 80 mg of tannic acid and add it to the mixed solution. Stir well and add 2 mL of 1.0 mol·L -1 The reaction was continued and stirred at room temperature for 5 minutes to promote the reaction to proceed fully. The above solution was centrifuged and washed with deionized water several times, and finally the washed product was placed in a vacuum dryer at 80°C overnight to obtain an amorphous metal oxide containing Cu element.
[0060] Fig. 9 There is no obvious diffraction peak in the XRD diffraction pattern, which proves the amorphous structure of the material.
[0061] Example 5
[0062] Weigh 0.2 g each of Pd(acac)2, FeCl3·9H2O, CoCl2·6H2O, NiCl2·6H2O, and CuCl2·2H2O, and dissolve them in 200 mL of ethylene glycol. Stir evenly to obtain a solution containing metal salts. Then weigh 400 mg of tannic acid and add it to the above solution. Stir evenly and add 10 mL of 1.0 mol·L -1The reaction was continued and stirred at room temperature for 30 minutes to promote the reaction. The solution was centrifuged and washed with deionized water several times. Finally, the washed product was placed in a vacuum dryer at 80°C overnight to obtain a multi-element amorphous metal oxide containing Mn, Fe, Co, Ni, and Cu elements.
[0063] Fig.10 The absence of obvious diffraction peaks in the XRD diffraction pattern proves the amorphous structure of the material. Fig.11 The metal element distribution shows that all metal elements are evenly distributed in the catalyst.
[0064] Comparative Example 4
[0065] Weigh 0.2 g of CoCl2·6H2O and dissolve it in 40 mL of diethylene glycol. Stir well to obtain a solution containing metal salts. Then weigh 80 mg of tannic acid and add it to the mixed solution. Stir well and add 2 mL of 1.0 mol·L -1 The reaction was continued and stirred at room temperature for 5 minutes to promote the reaction to proceed fully. The above solution was centrifuged and washed with deionized water several times, and finally the washed product was placed in a vacuum dryer at 80°C overnight to obtain an amorphous metal oxide containing Co element.
[0066] Fig.12 There is no obvious diffraction peak in the XRD diffraction pattern, which proves the amorphous structure of the material.
[0067] It can be seen from the above embodiments that the embodiment of the present application is a method for preparing an amorphous oxide with certain universality. The method is a liquid phase coprecipitation synthesis method, which utilizes the difference in electron density and diffusion dynamics between metal ions to quickly synthesize uniform amorphous oxides with adjustable disorder, and provides a new preparation process for the field of amorphous oxide synthesis. At the same time, the present invention has the advantages of energy saving, high production efficiency, simple and easy process, green and environmental protection, no need for complex post-processing, and has the characteristics of customizability and mass production.
[0068] The above embodiments are only used to help understand the method and core idea of the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.
[0069] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for synthesizing a metal oxide material, characterized in that: The following steps are involved: Step 1, selecting metal salts corresponding to five or more metal elements, dissolving all of the metal salts in a reducing substance containing a hydroxyl functional group, and stirring until the metal salts are completely dissolved to form a solution; the metal elements are Li, Na, K, Mg, Ca, Al, Ti, Cr, Mn, Fe, Co, Ni, Cu, Zn, Sr, Zr, Nb, Mo, Ru, Rh, Pd, Cd, Sn, Cs, La, Ba, Ce, Nd, W, Re, Ir, Pt and Bi; Step 2, adding tannic acid as a reducing agent into the solution, and continuously stirring to form a mixed solution; Step three, adding a base to the mixed solution for reaction, wherein the base is sodium hydroxide and / or potassium hydroxide, and separating to obtain a multinary amorphous metal oxide.
2. The method for synthesizing a metal oxide material according to claim 1, characterized in that: In the step 1, the metal salt is one or more of metal hydrochloride, nitrate, nitrite, sulfate and acetylacetonate.
3. The method for synthesizing the metal oxide material according to claim 2, characterized in that: In step 1, the metal elements are at least five of Mg, Ca, Al, Ti, Cr, Mn, Fe, Co, Ni, Cu, Zn, Sr, Zr, Nb, Mo, Ru, Rh, Pd, Cd, Sn, Cs, La, Ba, Ce, Nd, W, Re, Ir, and Pt.
4. The method for synthesizing a metal oxide material according to claim 1, characterized in that: In the step 1, the reducing substance is one of ethylene glycol, ethanol, ethanolamine, β-mercaptoethanol and diethylene glycol.
5. The method for synthesizing a metal oxide material according to claim 1, characterized in that: In the step 2, the concentration of tannic acid in the mixed solution is 0.1-5 g / L.
6. The method for synthesizing a metal oxide material according to claim 1, characterized in that: In the step three, 0.1-10 mol / L alkaline solution is added to the mixed solution to carry out reaction.
7. The method for synthesizing a metal oxide material according to any one of claims 1 to 6, characterized in that: In the step three, after the reaction, the final product is collected by centrifugation, washed with water, and dried to obtain a dry multi-component amorphous metal oxide.
8. The method for synthesizing a metal oxide material according to claim 7, characterized in that: In the step three, the rotation speed of the centrifugal separation is 7000-8000 rpm, and the time is 5-10 minutes.
9. The method for synthesizing a metal oxide material according to claim 8, characterized in that: In the step 3, the centrifugal separation is followed by washing with water for 5-10 times.
10. The method for synthesizing a metal oxide material according to claim 7, characterized in that: In the step 3, the drying comprises: placing the product after washing with water under vacuum drying at 50-90° C. overnight.
Citation Information
Patent Citations
Efficient oxygen evolution high-entropy amorphous oxide nano-catalyst as well as preparation method and application thereof
CN113621988A
Amorphous pentabasic transition metal-based electrocatalyst material as well as preparation method and application thereof
CN115058734A
Pasty insertion material for expanding the gum sulcus and its use
DE102008005469A1
Method for the preparation of a composition of nanoparticles of at least one crystalline metal oxide
US20060245998A1
Method of manufacturing complex metal oxide powder and amorphous complex metal oxide
US20080003161A1